Case report: Differential diagnosis of highly amplified anti-CD5 CAR T cells and relapsed lymphoma cells in a patient with refractory ALK positive anaplastic large cell lymphoma - Mu, Wei; Zhang, Meilan; Hu, Guang; Han, Yunfeng; Mao, Xia; Chen, Caixia; Shen, Kefeng; Dai, Zhenyu; Zhu, Xiaojian; Zhou, Xiaoxi; Huang, Liang; Ao, Qilin; et al. (Frontiers in Immunology, 2023)
Anaplastic Large Cell Lymphoma (ALCL) is one of the most common subtypes of T-cell lymphoma. Among these, refractory and relapsed (r/r) ALK positive ALCL lacks effective therapies. The chimeric antigen receptor-modified T (CAR-T) cell therapy holds great promise as a therapeutic strategy for this disease. However, it is not known yet whether anti-CD5 CAR-T cells are sufficient for the definitive treatment of relapsed ALK + ALCL, nor the role of accurate laboratory-based diagnoses during CAR-T treatment.The adolescent patient received autologous T cells containing sequences encoding VH domains specific to CD5. Following the infusion, there was an increase in both the copy number and proportion of CAR-T cells in peripheral blood. IL-6 and ferritin levels in the patient exhibited significant fluctuations, with increases of 13 and 70 folds respectively, compared to baseline after the treatment. Additionally, adverse effects were observed, including grade 4 rash, grade 1 headache, nausea, and neck-pain. Surprisingly, a relapsed disease phenotype was identified based on the results of PET/CT and histopathological analysis of the inguinal lymph node biopsy. After conducting a thorough diagnostic assessment, which included flow cytometry, next-generation sequencing (NGS), examination of immune-related gene rearrangements, and analysis of the immune repertoire of T-cell receptors (TCR), we conclusively determined that the hyperplastic T cells identified in the lymph node were the result of an expansion of CAR-T cells. Ultimately, the patient has attained complete remission (CR) and has sustained a disease-free survival state for 815 days as of the cutoff date on August 3 30, 2023.Taken together, the results demonstrate that anti-CD5 CAR-T cells can induce a clinical response in r/r ALK + ALCL patient. Furthermore, this case underscores the importance of utilizing advanced technologies with high sensitivity and accuracy for biological detection in clinical laboratory diagnosis and prognosis in CAR-T cell treatment.